(3fXe GdESJYGQIs - (3GdWHdGhj , efUhQ GdWHdGhj Hf SHW fGUQ GdOjf eMeO Hf SGde, SHW fGUQ GdOjf,J (B1014 (3g` s
(3ChdgG (B:s
(3jbhd SHW GdfGUQ GdWHdGhi efUhQ GdQGLi GdMfGf GdKGhi hGdBd hGdUMHg Chdi gPG hbO fXeJ GdESJYGQg edNUkG CbSGegG hMcegG ai gPg GdCHjGJ aGMaX fXegG s
(3BNQgG (B:s
(3heLGR LYdg GdJNjdjI eQTMkG cf GdJMjbjbg gPG EfNJGe eG bUOfG fXeg hGdMeO ddg hdi GdfYeg JeJ GdESJYGQI hGdMeO ddg hMOg s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B300 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B15s
Keywords: (3GdHdGZIs